THE INFLUENCE OF GAMIFICATION ON EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL PRODUCTIVITY IN COMPANY BUSINESS INNOVATION - Riatmaja, Dodi Setiawan; Sukmaningrum, Dinda; Supardin, Lalu (JURNAL EKBIS, 2024)
The problem with this research is the lack of empirical understanding of the impact of gamification on employee engagement and performance in a rapidly evolving business environment. The aim of this research is to analyze how gamification factors, including feedback, constructs, challenges, and stories, influence employee engagement and organizational productivity, with the hope of providing strategic insights for companies in improving employee performance in a competitive work environment. This research used 50 employees of a technology provider company. Data analysis in this research is SEM PLS. Research result. Gamification elements such as feedback, structure and story play a key role in increasing employee engagement. Analysis of the results shows that feedback, structure, and stories significantly contribute positively to employee engagement. Additionally, feedback and stories also have a positive impact on organizational productivity. Although structure has not been shown to have a significant effect on organizational productivity, this does not diminish the importance of feedback and stories as key factors in this context. On the other hand, the challenge element does not show a significant influence on either employee engagement or organizational productivity.